تجليات الفشل المدرسي ومخرجاته - بلخضر، محمد (المركز الجامعي أمين العقال الحاج موسى أق أخموك بتامنغست, 2020)
سنتطرق ضمن مقالنا هذا إلى ظاهرة تربوية متجددة في الحقل التربوي، والمتمثلة في أهم المؤشرات والتجليات ذات الصلة بالفشل المدرسي، والذي اكتسح المؤسسة التربوية، وهذا من خلال وصف إجرائي لأهم مراحل بروز هذه المشكلة، إضافة إلى إعطاء أهم القراءات النقدية التي فسرت هاته الظاهرة داخل المؤسسة التعليمية، مبرزين في ذلك أهم الأسباب والمتغيرات السوسيوتربوية، وكذا البيداغوجية للفشل المدرسي من جهة، وأهم النتائج والإفرازات التربوية من جهة أخرى، دون أن ننسى بعض الحلول التي تتماشى والمراحل الراهنة، لا سيما على المديين المتوسط والطويل، فهي ظاهرة تبرز داخل مؤسسة تخضع إلى التغير الثقافي والاجتماعي والاقتصادي الذي ينتجه المجتمع بمختلف مؤسساته.
In this article we will discuss a renewed educational phenomenon in the educational field, which is represented in the most important indicators and manifestations related to school failure, which swept the educational institution, and this is through a procedural description of the most important stages of the emergence of this problem, in addition to giving the most critical readings that explained this phenomenon within the institution Educational, highlighting the most important causes and sociological changes, as well as pedagogy for school failure on the one hand, and the most important educational results and secretions on the other hand, without forgetting some of the solutions that are consistent with the current stages, especially i the medium and long term, as it is a phenomenon that emerges within the institution It is subject to the cultural, social and economic change that society produces in its various institutions.
Keywords: الإدارة التعليمية -- علم الاجتماع التربوي -- التسرب الدراسي -- المؤسسات التربوية